2004
DOI: 10.1021/ja039052p
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivation of Self-Immolative Dendritic Prodrugs by Catalytic Antibody 38C2

Abstract: Self-immolative dendrimers have recently been developed and introduced as a potential platform for a multi-prodrug. These unique structural dendrimers can release all of their tail units, through a self-immolative chain fragmentation, which is initiated by a single cleavage at the dendrimer's core. Incorporation of drug molecules as the tail units and an enzyme substrate as the trigger can generate a multi-prodrug unit that will be activated with a single enzymatic cleavage. We have synthesized the first gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
169
0
5

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 208 publications
(179 citation statements)
references
References 21 publications
1
169
0
5
Order By: Relevance
“…2). It has been suggested that when drug molecules are attached as end groups at the periphery, the dendrimer can be used as an efficient drug delivery platform [25]. For latest developments in this direction the reader is referred to Refs.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…2). It has been suggested that when drug molecules are attached as end groups at the periphery, the dendrimer can be used as an efficient drug delivery platform [25]. For latest developments in this direction the reader is referred to Refs.…”
Section: Figurementioning
confidence: 99%
“…(22) and (24) it follows that the transition rates are given by (25) and is arbitrary. Note that has two components; the component of geometric origin, whereas e emerges from energetic consideration.…”
Section: Figrue 10mentioning
confidence: 99%
“…The unique architectural features of dendrimers offer additional elegant strategies to gain exquisite control over release of active drug. In particular, the production of dendrimers functionalized with catalytic antibodies [68] has spurred the development of dendrimers capable of ''selfimmolation'' [93][94][95].…”
Section: Release Of Covalently-delivered ''Pro-drugs''mentioning
confidence: 99%
“…To briefly explain, these unique assemblies have the ability to release all of their tail units (i.e., the active drug) through a self-immolative chain fragmentation, which is initiated by a single cleavage at the dendrimer's core [96]. The first generation of dendritic prodrugs was demonstrated by Shamis and coworkers who synthesized doxorubicin and camptothecin as tail units and designed a retro-aldol retro-Michael focal trigger provided by action of the catalytic antibody 38C2 [94]. This method showed a dramatic increase in toxicity to tumor cells upon bioactivation of the pro-drug compared with tests done in the absence of the activating antibody.…”
Section: Release Of Covalently-delivered ''Pro-drugs''mentioning
confidence: 99%
“…The excellent retro-aldolase activity (2, 3) of Abs 38C2 (4) and 93F3 (5) has allowed us to design, synthesize, and evaluate prodrugs of various chemotherapeutic agents that can be activated by retro-aldol reactions (6)(7)(8)(9)(10). In a syngeneic mouse model of neuroblastoma, systemic administration of an etoposide prodrug and intratumor injection of Ab 38C2 inhibited tumor growth (11).…”
mentioning
confidence: 99%